Three dimensional patient-specific collagen architecture modulates cartilage responses in the knee joint during gait. Issue 11 (17th August 2016) - Räsänen, Lasse P.; Mononen, Mika E.; Lammentausta, Eveliina; Nieminen, Miika T.; Jurvelin, Jukka S.; Korhonen, Rami K.
Abstract: Site-specific variation of collagen fibril orientations can affect cartilage stresses in knee joints. However, this has not been confirmed by 3-D analyses. Therefore, we present a novel method for evaluation of the effect of patient-specific collagen architecture on time-dependent mechanical responses of knee joint cartilage during gait. 3-D finite element (FE) models of a human knee joint were created with the collagen architectures obtained from T2 mapped MRI ( patient - specific model ) and from literature ( literature model ). The effect of accuracy of the implementation of collagen fibril architecture into the model was examined by using a submodel with denser FE mesh. Compared to the literature model, fibril strains and maximum principal stresses were reduced especially in the superficial/middle regions of medial tibial cartilage in the patient - specific model after the loading response of gait (up to −413 and −26%, respectively). Compared to the more coarsely meshed joint model, the patient - specific submodel demonstrated similar strain and stress distributions but increased values particularly in the superficial cartilage regions (especially stresses increased >60%). The results demonstrate that implementation of subject-specific collagen architecture of cartilage in 3-D modulates location- and time-dependent mechanical responses of human knee joint cartilage. Submodeling with more accurate implementation of collagen fibril architecture alters cartilage stresses particularly in the superficial/middle tissue.